1978
DOI: 10.1113/jphysiol.1978.sp012389
|View full text |Cite
|
Sign up to set email alerts
|

Functional distinction between two transport mechanisms in rabbit gall‐bladder epithelium by use of ouabain, ethacrynic acid and metabolic inhibitors.

Abstract: SUMMARY1. Net fluid transport rate, transepithelial p.d. and resistance, and unidirectional Na+-fluxes were measured in rabbit gall-bladder preparations exposed on both sides to bicarbonate-Ringer solution in vitro.2. Both ouabain and ethacrynic acid (ETCA) caused dose-dependent decreases of net fluid transport rate; ouabain inhibited fluid transport predominantly from the serosal side, whereas the inhibitory effect of ETCA was elicited mainly from the mucosal (luminal) side. Applied bilaterally, the ID50 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
3
2
0
Order By: Relevance
“…Therefore, the transepithelial PD of the rabbit gallbladder does not seem to be determined by any shunting effect in the paracellular pathway . Rather, the results support the previous conclusion (8,19,24) that the transepithelial transport mechanism in this epithe- Because the tight junctions in low resistance epithelia seem to comprise the pathway through which most of the passive diffusion of many smaller solutes take place, it has been postulated that this pathway may also serve as the route for a significant part of net transepithelial water transport (3,14,34). Recently, it has been suggested that all transepithelial net water flow in the Necturus gallbladder bypasses the epithelial cells (20) .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, the transepithelial PD of the rabbit gallbladder does not seem to be determined by any shunting effect in the paracellular pathway . Rather, the results support the previous conclusion (8,19,24) that the transepithelial transport mechanism in this epithe- Because the tight junctions in low resistance epithelia seem to comprise the pathway through which most of the passive diffusion of many smaller solutes take place, it has been postulated that this pathway may also serve as the route for a significant part of net transepithelial water transport (3,14,34). Recently, it has been suggested that all transepithelial net water flow in the Necturus gallbladder bypasses the epithelial cells (20) .…”
Section: Discussionsupporting
confidence: 86%
“…Control values of net mucosa-to-serosa fluid transport rates (To,), transepithelial PD, and RT obtained ---60 min after preparation were : Tvo , = -0.5 ttl -min-' -mg dryweight-'; PD = 2.9 ± 0.2 mV (mucosal side positive); and RT = 44.5 ± 2.6 ohm-cm'. These values are in agreement with previous observations and have been demonstrated to be nearly constant during at least 4 h of incubation (8,9) .…”
Section: Functional Observationssupporting
confidence: 93%
See 1 more Smart Citation
“…Gargus and Slayman (13) have reported that LM(TK-) cells contain a diuretic-sensitive Na+-K+ cotransport system, similar to that described in a variety of mammalian (14, 15, 17-23, [25][26][27] and avian (16,28) (11,21,29,30). It is therefore reasonable to expect that, at reduced extracellular K+ concentrations, the cotransport system should mediate the net efflux of KV.…”
Section: Effect Of Diuretics On Cation Fluxes In Lm(tk-) Cellsmentioning
confidence: 73%
“…The diuretic-sensitive cation cotransport systems that have been described in avian (McManus and Schmidt, 1978;Bakker-Grunwald, 1981) and mammalian (Chipperfield, 1980;Dunham et al, 1980;Tosteson, 1981) erythrocytes, Ehrlich ascites cells (Bakker-Grunwald et al, 1980, Geck et a]., 1980), and a variety of epithelial tissues (Frederiksen, 1978;Rindler et al, 1980) show a specific activation by C1-; and in some cases, a coupled flux of C1-has been demonstrated (Dunham et al, 1980;Geck et al, 1980;Haas et al, 1982). It was therefore of interest to examine Kf efflux in LM(TK-) cells under Cl--free conditions.…”
Section: Role Of Cl-mentioning
confidence: 99%